Using the Theory of Planned Behavior to Explain Expecting Couples Birth Preparedness Intentions in a Rural Setting: A Cross-Sectional Study from Rukwa, Southern Tanzania - Fabiola V. Moshi; Stephen M. Kibusi; Flora Fabian (Advances in Public Health)
Background. According to the Theory of Planned Behavior, an intention to carry out a certain behavior facilitates action. In the context of planning for birth, certain preparations and planning may better ensure maternal and neonatal survival. Little is known on the predictors of birth preparedness intention among expecting couples. The aim of this study was to determine the predictors of birth preparedness intentions among expecting couples. Methods. A community based cross-sectional study targeting pregnant women and their partners was performed from June until October 2017. A three-stage probability sampling technique was employed to obtain a sample of 546 couples A structured questionnaire based upon the Theory of Planned Behavior was used. The questionnaire explored three main domains of birth preparedness intentions. These three domains included (1) attitudes towards birth preparedness, (2) perceived subjective norms towards birth preparedness, and (3) perceived behavior control towards birth preparedness. Results. The vast majority of study participants had birth preparedness intentions. This included 521 (95.4%) pregnant women and 543 (99.5%) of their male partners. After adjusting for the confounders, the predictors of birth preparedness intentions among pregnant women were attitude (AOR=70.134, 95% CI=12.536-392.360, p<0.001) and perceived behavior control (AOR=7.327, 95% CI=1.545-34.761, p<0.05) which were significant. Among male partners, only attitudes (AOR=31.315, 95% CI=1.497-655.149, p<0.05) influenced the birth preparedness intention. Conclusion. Birth preparedness intention among male partners was higher compared to their female partners. The reason for the difference could be the concern each group puts on the issue of birth preparedness. Among the three domains of intention, attitude and perceived behavior control were statistically significant predictors of birth preparedness intention among pregnant women. Attitude was the only domain which influenced birth preparedness intention among male partners. Therefore, interventional studies are recommended targeting attitudes and perceived behavior control in order to boost birth preparedness intention.